ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI ORANG TUA DALAM MEMANFAATKAN ALAT-ALAT PERMAINAN EDUKATIF DI RUANG ANAK RS. BAPTIS KEDIRI - Sulistyarini, Tri; Prasetyorini, Trischa Hari (Jurnal Penelitian STIKES Kediri, 2010)
abstract   Background : For sick child who admitted at hospital, the child will experience the stress and generally parent also experience of anxiety because their child’s health condition, so that parent has not motivation in usage educative playing toys (APE= Alat Permainan Edukatif). Influence factor parent’s motivation in usage educative playing toys is age, education and knowledge. The objective of this research is to analyze the influence factor parent’s motivation in usage educative playing toys in Pediatric Ward Kediri Baptist Hospital. Method : This research was analytic descriptive. Samples were  48 respondents using purposive sampling. Independent variable was influence factor parent’s motivation and dependent variable was motivation. Then analyzed using the linear logarithm test with significant level 0,05. The value for factor of age p = 0,335, factor of education p = 0,094 and factor of knowledge p = 0,138. Conclusion : The Conclusion of this research was most dominant factor influenced the parent’s motivation in usage educative playing toys in Pediatric Ward Kediri Baptist Hospital.   Keyword : Motivation, Parent, Educative Playing Toys